COMPUTERIZED TOMOGRAPHY AND MAGNETIC RESONANCE IN VASCULAR ENCEPHALIC ACCIDENT (Fiep Bulletin - online, 2019)
Encephalic Vascular Accident (EVA) is one of the cerebrovascular diseases that causes great impact on the worldhealth and generates enormous social and economic costs (CONTIN, 2011). The EVA has a therapeutic window of 3 h forthe treatment, period in which it is possible to intervene in the ischemic or hemorrhagic lesion to diminish the damages(RAFFIN, 2002). Early and accurate diagnosis is fundamental because it is a medical emergency and only clinical evaluationof patients with suspected stroke is insufficient and incapable of differentiating whether the lesion is hemorrhagic or ischemic(SILVA, OLIVEIRA, 2017). The accepted imaging methods to initially evaluate are computed tomography (CT) and MagneticResonance (MRI) for examination of the skull. Computed tomography and magnetic resonance imaging are important in thecharacterization, identification, diagnostic confirmation of stroke and the removal of hypotheses from other causes,facilitating the rapid decision making regarding the use or not of thrombolytic therapy. Diagnosis by CT and MRI in EVAreliably helps to identify differences between irreversibly affected brain tissue and reversible tissue that may benefit fromearly treatment such as reperfusion, preventing cell death and reestablishing normal function (Silva, 2017). Each techniquehas advantages and disadvantages, being suggestive more studies that can compare through measures of greater precisionthe point efficiency among the techniques.
Keywords: “stroke”; “computed tomography”; “magnetic resonance”.